Improving workflows in community pharmacies for competitive advantage. (22nd May 2019) - Lockamy, Archie; Galdo, John A.
The purpose of this article is to provide a methodology for improving workflows in community pharmacies. Field research conducted at a community pharmacy along with academic literature in the areas of process management and workflow analysis form the basis for the conclusions and managerial implications provided in this article. The methodology illustrated in this article for improving workflows in community pharmacies can be used as a process enabler for enhanced efficiency and effectiveness through improved employee productivity, reduced labour cost, and enhanced employee satisfaction. The managerial implications regarding the methodology provided in the article can be used to facilitate a sustainable competitive advantage in the marketplace. The concepts presented in the article can be used by healthcare planners to improve the delivery of pharmaceutical goods and services within their organisations. This article begins to fill a void in the literature concerning how community pharmacies can continue to provide high quality patient counselling and remain profitable.